Commerce and colonization in the ancient near East - Aubet, María Eugenia, (Cambridge University Press, 2013)
"In this analysis, the roots of the Phoenician colonial system are traced and the metropolis of Tyre is established as the final link in a chain of experiences in the ancient Near East"--